Are the intraday effects of central bank intervention on exchange rate spreads asymmetric and state dependent? - Rasmus Fatum; Jesper Pedersen; Peter Norman Sørensen (University of California, Santa Cruz Institute for International Economics (SCIIE), 2010)
This paper investigates the intraday effects of unannounced foreign exchange intervention on bid-ask exchange rate spreads using official intraday intervention data provided by the Danish central bank. Our starting point is a simple theoretical model of the bid-ask spread which we use to formulate testable hypotheses regarding how unannounced intervention purchases and intervention sales influence the market asymmetrically. To test these hypotheses we estimate weighted least squares (WLS) time-series models of the intraday bid-ask spread. Our main result is that intervention purchases and sales both exert a significant influence on the exchange rate spread, but in opposite directions: intervention purchases of the smaller currency, on average, reduce the spread while intervention sales, on average, increase the spread. We also show that intervention only affects the exchange rate spread when the state of the market is not abnormally volatile. Our results are consistent with the notion that illiquidity arises when traders fear speculative pressure against the smaller currency and confirms the asymmetry hypothesis of our theoretical model.
Keywords: D53; E58; F31; G15; 330; Foreign Exchange Intervention; Exchange Rate Spreads; Intraday Data; Wechselkurspolitik; Geld-Brief-Spanne; Wechselkurs; Zeitreihenanalyse; Dänemark